Variations in radiation, total ozone and illumination during the solar eclipse of 20 May 1966 at New Delhi (MAUSAM, 1969)
A study has been made of the variations of solar and atmospheric radiation. total ozone content during the solar eclipse on 20 May 1966 with the help of available instruments at Radiation Laboratory. New Delhi. Variations in the values of the natural illumination derived from measurements of solar radiation on this day have also been studied and discussed.